(untitled) (Zaporizhzhia Historical Review, 2021)
The author studies a subject of ethnic development, which is specially actual in a modern world. Usage in the analysis of achievements of two sciences (archaeological and theoretical demography) has allowed receiving the new data. The general methodological approaches are conveyed in the article. The main attention is given to terrains of Black Sea Region and Crimea.